Penny Postcard Image of the Belltower and Arcade in Ojai, CA - United States Post Office::::::
Penny postcard image of Ojai, as it was rebuilt after the fire that destroyed the hamlet known as Nordoff, in 1917. The image shows the arcade on the left and the belltower, with Libbey Park beyond it, on the right. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.